Sustainable Development: Environmental, Economical, Social Well-Being for Today and Tomorrow - Sahin, Sagufta; Mete, Jayanta (MIMBAR PENDIDIKAN, 2016)
ABSTRACT: In 1987, the World Commission on Environment and Development stated that sustainable development is development meets the needs of the present without compromising the ability of future generations. Sustainable development constantly seeks to achieve social and economic progress in ways that will not exhaust the earthâ€™s finite natural resources. The needs of the world today are real and immediate, yet itâ€™s necessary to develop ways to meet these needs that do not disregard the future. The capacity of our ecosystem is not limitless, meaning that future generations may not be able to meet their needs the way we are able to now. The growth that is unmanaged and unsustained will lead to increased poverty and decline of the environment. We owe it to future generations to explore lifestyles and paths of development that effectively balance progress with awareness of its environmental impact. Sustainable development practices can help us do this; and through education and building awareness, preserving the future is within everyoneâ€™s reach. It is our duty to make people aware about the sustainable development and its importance for our future generation. In this paper, we will discuss that education is the only instrument which can provide knowledge on this particular respect to the common people.KEY WORD: Sustainable development, economic progress, educational awareness, future generations, and quality of life.Â ABSTRAKSI: â€œPembangunan Berkelanjutan: Lingkungan, Ekonomi, Kesejahteraan Sosial untuk Hari Ini dan Esokâ€. Pada tahun 1987, Komisi Dunia tentang Lingkungan dan Pembangunan menyatakan bahwa pembangunan berkelanjutan adalah pembangunan yang memenuhi kebutuhan saat ini tanpa mengorbankan kemampuan generasi mendatang. Pembangunan berkelanjutan terus berupaya untuk mencapai kemajuan sosial dan ekonomi dengan cara-cara yang tidak akan menguras sumber daya alam yang terbatas. Kebutuhan dunia saat ini adalah nyata dan segera, namun cara-cara untuk memenuhi kebutuhan tersebut yang tidak mengabaikan masa depan perlu dikembangkan. Kapasitas ekosistem kita tidak tak terbatas, yang berarti bahwa generasi masa depan mungkin tidak dapat memenuhi kebutuhan mereka dengan cara yang kita dapat sekarang. Pertumbuhan yang tak dikelola dan dilestarikan dengan baik akan mengakibatkan peningkatan kemiskinan dan penurunan kualitas lingkungan. Kita berutang kepada generasi mendatang untuk mengeksplorasi gaya hidup dan jalur pembangunan yang efektif dalam menyeimbangkan kemajuan dengan kesadaran dampak lingkungan. Praktek-praktek pembangunan berkelanjutan dapat membantu kita melakukan ini semua; dan melalui pendidikan dan penyadaran, pelestarian masa depan berada dalam jangkauan setiap orang. Adalah tugas kita untuk membuat orang sadar tentang pembangunan berkelanjutan dan pentingnya bagi generasi kita di masa depan. Dalam tulisan ini, kami akan membahas pendidikan sebagai satu-satunya alat yang dapat memberikan pengetahuan tentang hal ini, khususnya menghargai kepentingan umum.KATA KUNCI:Pembangunan berkelanjutan, kemajuan ekonomi, kesadaran pendidikan, generasi masa depan, dan kualitas hidup.Â Â About the Authors: Sagufta Sahin, M.Ed. is Ex-Student at the Department of Education, Kalyani University, Kalyani, Nadia, Pin-741235, West Bengal, India. Dr. Jayanta Mete is a Professor at the Department of Education, Kalyani University, Kalyani, Nadia, Pin-741235, West Bengal, India. Corresponding authors are: ssahin777@gmail.com and andjayanta_135@yahoo.co.in Â How to cite this article? Sahin, Sagufta Jayanta Mete. (2016). â€œSustainable Development: Environmental, Economical, Social Well-Being for Today and Tomorrowâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.1(1) Maret, pp.1-12. Bandung, Indonesia: UPI Press. Chronicle of the article: Accepted (January 8, 2016); Revised (February 8, 2016); and Published (March 11, 2016).